Designing a model of indifference in theorizing in management research with grounded theory approach - Asgharinajib, Maryam; Aalipour, Sima; Sorooshian, Shahryar (Frontiers in Research Metrics and Analytics, 2024)
This study explores and elucidates the phenomenon of indifference in theorizing within management research in Iran, highlighting the causal conditions and implications of this indifference on both the academic and practical landscapes of management. Using a qualitative grounded theory methodology, this study synthesized the data collected through interviews with management faculty members from various Iranian universities. Purposive sampling was employed to select participants until theoretical saturation was achieved with 29 interviews. The data were analyzed using ATLAS.ti software, enabling the construction of a paradigm model to explain the observed phenomena. The study identified multiple causal conditions contributing to indifference in theorizing, including individual, educational, cultural, economic, social, political, and systemic factors. These factors collectively foster a climate of scientific isolation, hindering the development of management theories and affecting both educators and students. The outcomes of this indifference manifest as a reduction in theoretical innovation and diminished engagement with management theory among academics and practitioners. Indifference, as a key concept in the presented model, represents a type of scientific silence, indicating the unwillingness or inability of researchers to create new and effective theories in the field of management. This research contributes to the field by providing a detailed model of the dynamics underlying indifference in theorizing within management studies in Iran, a topic that has received limited attention in the existing literature. The study's findings emphasize the need for systemic changes to overcome barriers to theorizing and suggest pathways for revitalizing theoretical contributions in management research.